ALDH1: A potential therapeutic target for cancer stem cells in solid tumors - Wei, Yaolu; Li, Yan; Chen, Yenan; Liu, Pei; Huang, Sheng; Zhang, Yuping; Sun, Yanling; Wu, Zhe; Hu, Meichun; Wu, Qian; Wu, Hongnian; Liu, Fuxing; et al. (Frontiers in Oncology, 2022)
Solid tumors can be divided into benign solid tumors and malignant solid tumors in the academic community, among which malignant solid tumors are called cancers. Cancer is the second leading cause of death in the world, and the global incidence of cancer is increasing year by year. New cancer patients in China are always the first. After the concept of stem cells was introduced in the tumor community, CSC markers represented by ALDH1 have been widely studied because of their strong CSC cell characteristics and their potential to be the driving force of tumor metastasis. In the research results in the past five years, it has been found that ALDH1 is highly expressed in various solid cancers such as breast cancer, lung cancer, colorectal cancer, liver cancer, gastric cancer, cervical cancer, esophageal cancer, ovarian cancer, head and neck cancer. ALDH1 can activate and transform various pathways (such as USP28/MYC signaling pathway, ALDH1A1/HIF-1α/VEGF axis, wnt/β-catenin signaling pathway), as well as changing the intracellular pH value to promote the formation and maintenance of tumors, resulting in drug resistance in tumors. By targeting and inhibiting ALDH1 in tumor stem cells, it can enhance the sensitivity of drugs and inhibit the proliferation, differentiation and metastasis of solid tumor stem cells to a certain extent. This review discusses the relationship and pathway of ALDH1 with various solid tumors, and proposes that ALDH1 may serve as diagnosis and therapeutic target for CSC, providing new insights and new strategies for solid tumor treatment.